Minion - Anderson, John David, 1975- (Walden Pond Press, 2015)
In a city without a superhero, Michael Morn lives with his dad using his special "gift" to help them get by. So when one day a Super named Comet comes to town, everything changes. Comet threatens the life Michael and his dad have built, and may force Michael to become a Villain.